2021
DOI: 10.3390/cancers13225866
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Activity of Expanded PBMC-Derived NK Cells by Feeder-Free Protocol in Ovarian Cancer

Abstract: Natural killer (NK) cells have shown great therapeutic potential against a wide range of cancers due to their pan-specific target recognition. Numerous reports indicate that NK cell immunotherapy is an effective therapeutic approach for treating hematological malignancies, but shows limited effects against solid tumors. In this study, several models of ovarian cancer (OC) were used to test the anti-cancer effects of NK cells derived from human peripheral blood mononuclear cells and expanded using a feeder cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 47 publications
(65 reference statements)
5
16
0
Order By: Relevance
“…Our previous studies demonstrated that ex vivo expanded PBMC-derived NK cells by the defined feeder-free protocol effectively reduced the tumor burden and ascites in a xenograft murine OC model [ 29 ]. scFvCD16A-sc4-1BBL can stimulated the activation and expansion of NK cells from PBMCs in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies demonstrated that ex vivo expanded PBMC-derived NK cells by the defined feeder-free protocol effectively reduced the tumor burden and ascites in a xenograft murine OC model [ 29 ]. scFvCD16A-sc4-1BBL can stimulated the activation and expansion of NK cells from PBMCs in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Adoptive transfer of NK cells can recognize and kill tumor cells without MHC restriction, so it may be a better option to drive NK cells to treat ovarian cancer [ 63 , 67 , 68 ]. Previous studies in our laboratory showed that the adoptive transfer of PBMC-derived NK cells expanded by a feeder-free protocol combined with rhIL-2 effectively inhibited the growth of ovarian tumors in mice [ 29 ]. Here, we utilized this model and illustrated that scFvCD16A-sc4-1BBL enhanced the anti-solid tumor effect of NK cells without observed toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations